Figures of sanctity. Semiotics, sacred texts and theory of culture - Paolo Bertetti (Ocula)
In A.J. Greimas' generative semiotics an element in a text is considered figurative (i.e., it is a "figure") if it has a counterpart in the natural world. Greimas uses the expression 'natural world' (taken, mutatis mutandis, from Merleau-Ponty) to refer to the world of sense experience, fully organized and culturalized, and therefore already significant and endowed with meaning. In fact, figures are not simply "objects" belonging to the world they refer to: they originate from perception but are elements of a cultural nature that are already semiotically organized. This study aims to show how the analysis of the figurative component of meaning can contribute to the study of the religious discourse and in particular to the study of the imaginary and the model of Sanctity. To do this, we will first briefly present the semiotic concept of "figure", then we will see how the figurative analysis has been used in the study of biblical discourse by the scholars of the Centre pour l'Analyse du DIscours Religieux (CADIR) of the Catholic University of Lyon. Finally, we will present some examples of analysis that extend the figurative analysis to the more general study of the religious imagery.